A Depression Screening Protocol for Patients With Acute Stroke: A Quality Improvement Project. Issue 1 (February 2017) - McIntosh, Celia
Abstract : ABSTRACT: Background: Depression after stroke is common and is associated with poor functional recovery, suicidal ideation, decreased quality of life, and increased mortality. Despite this knowledge, poststroke depression (PSD) is often underdetected and thus undertreated. PSD is clinically important for the caregiver, the family, and the stroke survivor. Inconsistencies in screening and treatment practices may further contribute to these negative outcomes.Purpose: The purposes of this evidence-based clinical scholarship project were to (1) determine the efficacy of an evidence-based depression screening protocol in improving early detection and treatment of PSD and (2) identify if there were any relationships between the protocol interventions, depression scores, and diagnosis.Methods: A retrospective chart review was conducted in a convenience sample of 79 hospitalized patients with acute stroke. Depression was assessed using the Patient Health Questionnaire-9. Demographic data and medical and protocol variables were also collected. Descriptive statistics, chi-square test, and Pearson correlation test were used for data analysis.Results: Of the 79 participants, 56% were men, 65% were White, 77% were admitted with ischemic stroke, and 48% were identified as being depressed (Patient Health Questionnaire-9 depression scale > 4). Individuals with a history of depression (χ 2 = 17.09, p = .002) were also more likely to have higher levels of depression severity as compared with patients who did not have a history of depression. After the intervention, patients screening positive were more likely to receive an educational booklet on stroke and depression (χ 2 = 30.0, p = .000) and be medically treated for PSD before discharge (χ 2 = 5.57, p = .018). Nurses' documentation of screening results also improved (χ 2 = 9.19, p = .002).Conclusion: Implementation of the Evidence Based Depression Screening and Treatment (EBDST) protocol improved early detection and treatment of PSD in the hospitalized patients with acute stroke before discharge. The EBDST protocol promoted systematic evidence-based depression screening in the hospitalized patients with acute stroke. Use of the EBDST protocol may further improve long-term health outcomes, decrease mortality, and improve functional recovery and quality of life.